Immobilization of b-Galactosidase from Aspergillus oryza on Magnetic Poly(GMA-ST) Beads - Sun, Sufang; Zhao, Xiuying; Xu, Xiaobing (Asian Journal of Chemistry, 2012)
In this study, novel magnetic beads were prepared from glycidylmethacrylate (GMA) and styrene (ST) via suspension polymerization with cyclohexanol and lauryl alcohol as porogenic agent. The magnetic poly (GMA-ST) beads were characterized with scanning electron microscope (SEM), magnetic scales and X-ray spectroscopy. The magnetic susceptibility of the porous poly (GMA-ST) beads was 1.25 × 10-4 cm3/g. Under the optimum conditions, b-galactosidase was immobilized on the magnetic poly (GMA-ST) beads described above, the results obtained showed that the activity of the immobilized b-galactosidase reached 412.09 U/g and the activity recovery was 61.32 %. Finally, the basic properties of the immobilized enzyme were determined separately and satisfactory results were obtained in pH stability, thermal stability, operational stability and Michaelis constants Km.